Do occupational pension funds monitor companies in which they hold large stakes? - Faccio, Mara; Lasfer, M.Ameziane (Journal of Corporate Finance, 2000)
In this paper we analyze the monitoring role of occupational pension funds in the UK. We argue that because of their objectives, structure and overall share holding, occupational pension funds are likely to have more incentives to monitor companies in which they hold large stakes than other financial institutions. By comparing companies in which these funds hold large stakes with a control group of companies listed on the London Stock Exchange, we show that occupational pension funds hold large stakes over a long-time period mainly in small companies. However, the value added by these funds is negligible and their holdings do not lead companies to comply with the Code of Best Practice or outperform their industry counterparts. Overall, our results suggest that occupational pension funds are not effective monitors.